Mapping of QTLs for morphophysiological and yield traits under water-deficit stress and well-watered conditions in maize - Sarkar, Basudeb; Varalaxmi, Yellisetty; Vanaja, Maddi; RaviKumar, Nakka; Prabhakar, Mathyam; Yadav, Sushil Kumar; Maheswari, Mandapaka; Singh, Vinod Kumar (Frontiers in Plant Science, 2023)
Drought is the major abiotic stress affecting worldwide maize productivity. The present study was aimed to map genomic regions associated with drought tolerance related morpho-physiological and yield traits by phenotyping RIL mapping population under well-watered and water-deficit stressed conditions for two seasons and SNP genotyping following genotyping-by-sequencing approach. Also, using sequencing data, effort was made in mining of candidate genes responsible for phenotypic variation for understanding the molecular mechanism of drought tolerance in maize. Phenotyping of RILs population showed high variability for most of the traits with normal frequency distribution, indicating their polygenic nature. The linkage map was generated using 1241 polymorphic SNPs distributed over 10 chromosomes covering a total genetic distance of 5471.55cM. A total of 27 QTLs were identified for the various morpho-physiological and yield related traits under well-watered (13) and water-deficit stressed conditions (12). One common major QTL (qCW2-1) for cob weight and a minor QTL (qCH1-1) for cob height was stably identified at both of the water regimes. A major and a minor QTL was detected for NDVI under water-deficit stressed conditions on chromosome 2 (bin 2.10). One major (qCH1-2) and one minor (qCH1-1) QTL identified on chromosome 1 in our study, was located at different genomic position than earlier studies. The Co-localized QTLs for stomatal conductance and grain yield on chromosome 6 (qgs6-2, qGY6-1); stomatal conductance and transpiration rate on chromosome 7 (qgs7-1, qTR7-1) were detected. The function of major candidate genes associated with QTLs detected under water-deficit stressed were related to growth and development, senescence, ABA signalling, signal transduction and transporter activity in imparting stress tolerance. The QTL regions identified in this study could be useful in designing SSR primers and can be used in marker assisted selection breeding. The putative candidate genes can be isolated and functionally characterized for understanding its role in imparting drought tolerance.